Relaxational Dynamics in the PYR14-IM14 Ionic Liquid by Mechanical Spectroscopy - Paolone,Annalisa (2018)
The anelastic spectrum of the N-butyl-N-methyl-pyrrolidinium (triﬂuoromethanesulfonyl) (nonaﬂuorobutanesulfonyl)imide (PYR14-IM14) is reported for the first time. On cooling, at 4 Kmin-1 the sample undergoes a glass transition around 190 K. In the liquid phase, a thermally activated relaxation process is measured and it is analyzed by means of a modified Debye model. The best fit results indicate that the peak is related to the ion hopping between non-equivalent configurations which are mainly defined by the anion conformer configuration.